2001 Proceedings. 51st Electronic Components and Technology Conference (Cat. No.01CH37220)
DOI: 10.1109/ectc.2001.927679
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated double-bump WL-CSP: design and reliability

Abstract: A new type of wafer level package has been designed and fabricated by using an encapsulation material, which is applied directly to a bumped wafer, thereby eliminating the underfill process, and protecting all the bumps on the wafer at once in a batch process. This material was designed to have the necessary elastic modulus and coefficient of thermal expansion required by this application. After application of the encapsulation, the wafer is then bumped again with C5 balls, creating a double bump structure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Although a large number of studies have been done on WL-CSP [3] [4], it is difficult to apply WL-CSP to topography wafer, such as MEMS and stacked ICs. The main reason is that it makes it difficult to apply photolithography process to make traces, vias, and ball grid array (BGA) lands.…”
Section: Fig1 Block Diagram Of Rf Variable Capacitor Mems and Driver Icmentioning
confidence: 99%
“…Although a large number of studies have been done on WL-CSP [3] [4], it is difficult to apply WL-CSP to topography wafer, such as MEMS and stacked ICs. The main reason is that it makes it difficult to apply photolithography process to make traces, vias, and ball grid array (BGA) lands.…”
Section: Fig1 Block Diagram Of Rf Variable Capacitor Mems and Driver Icmentioning
confidence: 99%
“…It is generally conceived that the high compliance of polymer film (e.g., low Young's modulus) results in solder joint stress reduction [10]. Ball shape, geometry, standoff height, and material also play an important role in thermo-mechanical performance of WLPs [11][12][13][14][15][16]. Previous works have demonstrated that a greater standoff height with a slim ballshape offer improved reliability performance.…”
Section: Introductionmentioning
confidence: 99%
“…Major developments on WLP are being performed on wafer bumping and different solutions and confip-ations are proposed by companies and laboratories [3,4,5]. The aim is to reduce the connection stress and achieve good reliability without having to perform individual underfill after Flip-Chip hybridization on board which is a costly operation.…”
Section: Introductionmentioning
confidence: 99%